2020
DOI: 10.17707/agricultforest.66.1.08
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Responses of Two Sugarcane Varieties to Whitefly Neomaskellia Andropogonis Infestation and Its Control by a New Butenolide Insecticide, Flupyradifurone

Abstract: Sugarcane whitefly, Neomaskellia andropogonis Corbett (Homoptera: Aleyrodidae), is established in the sugarcane ecosystem of Khuzestan Province, and it is one of the most important pests of sugarcane. Two fields of the CP69-1062 and IRC99-02 varieties of sugarcane were selected for evaluation of their biochemical responses, including pigment content, nitrogen, total protein, phosphorus and soluble sugars, to N. andropogonis infestation. Also, the efficiency of a new butenolide insecticide, flupyradifurone , wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…However, Nikpay (2017) reported that as the relative humidity increases the population of whitefly is enhanced till the 21 st of October, while the population is reduced as the temperature declines. In contrast, Saeedi (2020) reported that the pupal population of whitefly reached its peak (156 pupae per leaf) on 27 th October. Second Year Screening Trial Varietal Differences: The same fifteen genotypes were again screened in 2016 under similar ecological conditions.…”
Section: Resultsmentioning
confidence: 93%
“…However, Nikpay (2017) reported that as the relative humidity increases the population of whitefly is enhanced till the 21 st of October, while the population is reduced as the temperature declines. In contrast, Saeedi (2020) reported that the pupal population of whitefly reached its peak (156 pupae per leaf) on 27 th October. Second Year Screening Trial Varietal Differences: The same fifteen genotypes were again screened in 2016 under similar ecological conditions.…”
Section: Resultsmentioning
confidence: 93%
“…The most important indicators of priority and superiority of autumn-sown sugar beet cultivation compared with spring cultivation are the use of rainfall during the growth period, higher yield, fewer pests and diseases, and especially less water demand and high water use efficiency. This issue becomes doubly important because the lack of water resources is the most important challenge and limiting factor in the production of agricultural products in the country (Fasahat et al, 2018;Saeedi and Ziaee, 2020). The development of autumn-sown sugar beet cultivation and the supply of a part of sugar beet needed by sugar factories in areas that are facing limited water resources can be very important in the sustainability of sugar beet production in those areas.…”
Section: Introductionmentioning
confidence: 99%